(untitled) - Allen, G. C. (New York, 1940)
The purposw of this study is to examine the present condition of Japanese industry and to estimate the probable future line of development. The study is primarily concerned with the results of the impact of the present Sino-Japanese war on Japan's industrial structure.
Keywords: Công nghiệp,Industries; Nhật Bản,Japan